Education in Ukraine and Covid-19: New Perspectives and Opportunities - Tatiana Suhak, Iryna Shtuler, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Officially, the COVID-19 pandemic reached Ukraine in March 2020 and came to Ukraine at a time when the national economy was not in the best condition. In fact, the COVID-19 pandemic has transformed not only the structure of the national economy, but also the way of doing business. This is evidenced by indicators that reflect changes in the structure of gross domestic product, changes in the structure of employment and marketing tools. The COVID-19 pandemic has already led to a financial crisis and a crisis in certain areas and sectors of the economy, but there are those who have benefited from quarantine measures. However, there are industries and areas of activity for which the COVID-19 pandemic has given a good start and revenue growth. Timely response and targeted action will reduce the negative impact of the COVID-19 pandemic, prevent a decline in business activity, create conditions for the development of Ukrainian manufacturers and reduce the impact of the crisis caused by the COVID-19 pandemic.